Molecular basis of hypoxia-induced pulmonary vasoconstriction: role of voltage-gated potassium channels - Coppock, Elizabeth Ann, author; Tamkun, Michael M., advisor; Tucker, Alan, advisor; McMurtry, Ivan F., committee member; Beam, Kurt, committee member; Bowen, R. A., committee member (Colorado State University. Libraries, 2001)
Pulmonary artery smooth muscle cells (PASMCs) isolated from small resistance pulmonary arteries depolarize and contract in response to hypoxia while PASMCs isolated from large conduit arteries usually do not respond. The hypoxia-induced membrane depolarization, smooth muscle cell contraction, and subsequent constriction of resistance pulmonary arteries, is thought to occur via inhibition of PASMC K+ channels that are open at the resting membrane potential. As inhibition of these channels has been clearly implicated as an important step in hypoxic pulmonary vasoconstriction (HPV), recent attention has focused on identifying the K+ channel(s) involved in this response. Previous studies implicated a delayed-rectifier voltage-gated K+ (Kv) channel in both the maintenance of the resting membrane potential, and the hypoxia-induced depolarization of PASMCs from resistance arteries. Although progress has been made in identifying which Kv channel proteins are expressed in PASMCs, there are conflicting reports regarding which channels contribute to the native O2-sensitive K+ current. In this study, the O2-sensitivity of cloned Kv channels, expressed in a heterologous expression system, and the expression of Kv channel α and β subunits along the pulmonary arterial tree were examined in order to identify, from a molecular perspective, which Kv channels are likely to contribute to the O2-sensitive current expressed in resistance PASMCs. Additionally, since the targeting of Kv channels to lipid raft microdomains rich in signaling molecules, such as protein kinases, could represent a mechanism by which hypoxia alters Kv channel function, the targeting of the O2-sensitive Kv channel, Kv2.1, to lipid rafts was examined in PASMCs from conduit and resistance vessels. The effects of hypoxia on Kv1.2, Kv1.5, Kv2.1 and Kv9.3 α subunits expressed in mouse L-cells were examined using the whole-cell configuration of the patch-clamp technique. Hypoxia (PO2 ~ 30 mmHg) reversibly inhibited Kv1.2 and Kv2.1 currents at potentials more positive than 30 mV. In contrast, hypoxia had no effect on Kv1.5 current. Currents generated by the coexpression of Kv2.1 with Kv9.3 α subunits were reversibly inhibited by hypoxia in the voltage range of the resting membrane potential as were currents generated by the coexpression of Kv1.2 and Kv1.5 α subunits. These results indicate that 1) Kv1.2 and Kv2.1, but not Kv1.5, homomeric channels are reversibly inhibited by hypoxia, 2) Kv1.2 and Kv1.5 a subunits can assemble to form a functional heteromeric channel that is sensitive to hypoxia, and 3) only the heteromeric channels, Kv1.2/Kv1.5 and Kv2.1/Kv9.3, are inhibited by hypoxia in the voltage range of the PASMC resting membrane potential, suggesting that these heteromeric channels are likely components of the native pulmonary arterial O2-sensitive K+ current. In the second part of this study, expression of Kv1.2, Kv1.5, Kv2.1 and Kv3.1b was confirmed and expression of K vβ1.1, Kvβ1.2, Kvβ1.3, but not Kvβ2.1, channel proteins was demonstrated in PASMCs from conduit and resistance vessels. Additionally, immunoblotting with densitometry was used to demonstrate that expression levels of Kv3.1b and Kvβ1.1, Kvβ1.2 and Kvβ1.3, dramatically increases from the main conduit pulmonary artery to the small resistance pulmonary arteries where HPV is thought to occur. The expression level of Kv1.5 protein was modestly greater in resistance than in conduit PASMCs, while expression levels of both Kv1.2 and Kv2.1 channel proteins were similar between conduit and resistance PASMCs. Furthermore, mRNA levels of Kv9.3 appeared to be greater in resistance than in conduit PASMCs. The differential expression of Kv3.1b and Kv9.3 α subunits and members of the Kvβ1 subfamily suggests that they may be involved in the differential responses of conduit and resistance pulmonary arteries to hypoxia. In the third part of the study the targeting of Kv2.1 to lipid rafts in the pulmonary artery was examined. It was demonstrated that Kv2.1 targets to lipid rafts in both conduit and resistance PASMCs. It is not likely that Kv2.1 raft association alone accounts for the differential responses of conduit and resistance pulmonary arteries to hypoxia; however, the targeting of Kv channels to these important signaling centers may prove to be a key component of PASMC O2-sensing.
Keywords: anatomy and physiology; animals; biophysics